Reirradiation clinical practice in gastrointestinal abdominal malignancies: an international reirradiation collaborative group (ReCOG) systematic review - Malik, Nauman H.; Plastaras, John P.; Corradini, Stefanie; Dawson, Laura A.; Hawkins, Maria A.; Salerno, Kilian E.; Mayo, Charles S.; Dunne, Emma M.; Gabryś, Dorota; Grassberger, Clemens; Lawrence, Theodore S.; Sharma, Manju; et al. (Clinical and Translational Radiation Oncology, 2025)
Purpose: Reirradiation in abdominal malignancies has grown more common with advanced radiotherapy techniques. However, clinical use and implementation varies, and there remains limited consensus on best practices for reirradiation. In this systematic review, a multidisciplinary team treating gastrointestinal and hepatobiliary malignancies within the Reirradiation Collaborative Group (ReCOG) convened to review published literature on reirradiation in the abdomen to offer insights into patient selection, radiotherapy planning, risk management, and assessing knowledge gaps for future development of guidelines. Methods and Materials: A systematic search of Cochrane Central, CINAHL Plus, EMBASE, and PubMed up to August 30, 2024, was conducted as per Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) framework. Data on patient characteristics, radiation doses, dose constraints, treatment outcomes, and toxicities were extracted. Where feasible, pooled weighted analyses were performed. Results: Thirty-three studies involving 1,264 patients met inclusion criteria: 30 were retrospective and 3 prospective. The median number of patients reported per study was 26 (range 2–245). Of the reported tumor sites, 718 patients had liver tumors and 277 pancreas, with smaller numbers of mixed/lymph node targets. Reirradiation doses, fractionation schemes, and dose constraints varied widely; only half of the studies provided explicit organ-at-risk constraints. Three studies included patients treated with palliative intent. Median overall survival ranged from 5.9 to 44 months, with a pooled weighted median OS of 19.6 months across 20 studies that reported it. One-year local control rates ranged from 19 % to 93 %, with severe (grade ≥ 3) toxicities typically reported in 5–15 % of patients, although one study reported 25 % lethal RILD in liver reirradiation. Conclusion: Reirradiation in abdominal malignancies appears to be able to achieve meaningful local control and survival in select patients, though heterogeneity in planning, dosing, and toxicity reporting remains a major challenge for establishing best practices. Standardized reporting of doses, constraints, and dose-volume relationships are needed to guide safe and effective reirradiation in this setting.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Gastrointestinal cancers; Hepatocellular carcinoma; Liver metastases; Palliative radiotherapy; Recurrence; Reirradiation; Review; Salvage radiotherapy; Stereotactic body radiotherapy; Toxicity